A study on Bumiputera entrepreneur participation in online marketing area Kota Kinabalu / Mohd Reeza Amir Hamzah - Amir Hamzah, Mohd Reeza (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2014)
The primary objective of this study is to obtain the factors contribute to the Bumiputera entrepreneur participations in online Marketing. The study was conducted from currently news and data that gain from Bumiputera entrepreneur area Kota Kinabalu. It is give inspiration for researcher to obtain the data from lenses of Bumiputera entrepreneurs. For This purpose, 120 questionnaires were distributed, of which return in fully and very usable for data analysis. Survey results indicate that most of the Bumiputera entrepreneurs still not fully utilize online marketing as tools to deliver their products. This figure should enough for the Bumiputera entrepreneurs and other researcher to investigate and research deeply for future marketing plan. Taken action was very important to make Bumiputera entrepreneurs compete very well in market not only in Malaysia, but to the world that not have boundaries to deliver their product using online marketing.